DEVELOPMENT OF KEY COMPETENCIES AND ICT TEACHING AT UJS IN KOMARNO - SZOKOL, Stefan; Sandor, ALBERT (Trends in education, 2009)
The aim of the subject Informatics is to provide students with proper information literacy that is necessary to finish their studies and is essential in our information society. Information and communication technologies play an important role in university studies. Students are expected to learn on their own whilst using modern technologies. To support this, subjects that create preconditions for this process, can be found in the first year study program.
Keywords: key competencies; ICT; standards; information literacy.